ANALISIS SELF-DISCLOSURE PADA FENOMENA HYPERHONEST DI MEDIA SOSIAL - Radja Erland Hamzah; Citra Eka Putri (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Many of social media users still think that social media is a medium that is able to solve every problem of life. The function of social media has now experienced a shift in meaning from just a substitute for direct interaction to the stage of expressing oneself or self-disclosure even though in very diverse ways including being too honest in telling their life problems in cyberspace, the phenomenon of sharing personal privacy to vent excessively on social media is also referred to as hyperhonest. This study aims to analyze self-disclosure or self disclosure on hyperhonest phenomena on social media, seeing so many social media users sharing their privacy stories to cyberspace. The purpose of this study is to analyze the self-disclosure of kite breakers status on the Hyperhonest phenomenon on social media. The results of the study there are three things that encourage a person to express themselves on social media in the hyperhonest phenomenon, namely, first vent social media gives a sense of pleasure, second, the fulfillment of the need to be heard and third, the need to be known. This research uses social media theory, Self Disclosure theory and CPM (Communication Privacy Management) theory. This research is a qualitative research with case study research method.